Pulpwood Felling and Conversion by Different Felling Implements-a Comparative Study - Mitra, S. K.; Sood, K. G. (Indian Forester, 1977)
In developed countries Power Chain Saws have almost replaced the other hand tools for felling and conversion of trees. It was considered necessary to investigate whether the Power Chain Saw holds the same position in India. A comparative study was designed and conducted to find out the best tool for felling, cross cutting, delimbing for the preparation of unbarked pulpwood billets. For these operations three tools vis., Cross Cut Saw, Bow Saw and Power Chain Saw were used in Bijnor Plantation Division of U.P. for felling and convertion of Eucalyptus hybird. It was observed that Power Chain Saw is not economical under Indian condition for pulpwood harvesting. The study has indicated that although the output per man hour may increase considerably along with consequent saving in manpower due to the introduction of Power Chain Saw, the cest per unit volume of unbarked pulpwood billets Would not be reduced.